Problemy związane z występowaniem substancji humusowych w wodach podziemnych = Problems associated with humic substances in the groundwater - Krupińska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Humic substances are included in a group of most widespread organic compounds on the Earth. The paper includes review of literature concerning structure, the physico-chemical properties of humic substances and their impact on quality of groundwater and treatment.
Keywords: substancje humusowe; oczyszczanie wód podziemnych; humic substances; treatment of groundwaters